Human Tick-Borne Diseases in Australia - Dehhaghi, Mona; Kazemi Shariat Panahi, Hamed; Holmes, Edward C.; Hudson, Bernard J.; Schloeffel, Richard; Guillemin, Gilles J. (Frontiers in Cellular and Infection Microbiology, 2019)
There are 17 human-biting ticks known in Australia. The bites of Ixodes holocyclus, Ornithodoros capensis, and Ornithodoros gurneyi can cause paralysis, inflammation, and severe local and systemic reactions in humans, respectively. Six ticks, including Amblyomma triguttatum, Bothriocroton hydrosauri, Haemaphysalis novaeguineae, Ixodes cornuatus, Ixodes holocyclus, and Ixodes tasmani may transmit Coxiella burnetii, Rickettsia australis, Rickettsia honei, or Rickettsia honei subsp. marmionii. These bacterial pathogens cause Q fever, Queensland tick typhus (QTT), Flinders Island spotted fever (FISF), and Australian spotted fever (ASF). It is also believed that babesiosis can be transmitted by ticks to humans in Australia. In addition, Argas robertsi, Haemaphysalis bancrofti, Haemaphysalis longicornis, Ixodes hirsti, Rhipicephalus australis, and Rhipicephalus sanguineus ticks may play active roles in transmission of other pathogens that already exist or could potentially be introduced into Australia. These pathogens include Anaplasma spp., Bartonella spp., Burkholderia spp., Francisella spp., Dera Ghazi Khan virus (DGKV), tick-borne encephalitis virus (TBEV), Lake Clarendon virus (LCV), Saumarez Reef virus (SREV), Upolu virus (UPOV), or Vinegar Hill virus (VINHV). It is important to regularly update clinicians' knowledge about tick-borne infections because these bacteria and arboviruses are pathogens of humans that may cause fatal illness. An increase in the incidence of tick-borne infections of human may be observed in the future due to changes in demography, climate change, and increase in travel and shipments and even migratory patterns of birds or other animals. Moreover, the geographical conditions of Australia are favorable for many exotic ticks, which may become endemic to Australia given an opportunity. There are some human pathogens, such as Rickettsia conorii and Rickettsia rickettsii that are not currently present in Australia, but can be transmitted by some human-biting ticks found in Australia, such as Rhipicephalus sanguineus, if they enter and establish in this country. Despite these threats, our knowledge of Australian ticks and tick-borne diseases is in its infancy.